Integrated framework for stakeholder participation: Methods and tools for identifying and addressing human–wildlife conflicts. Issue 3 (11th March 2021) - König, Hannes J.; Ceaușu, Silvia; Reed, Mark; Kendall, Helen; Hemminger, Karoline; Reinke, Henrik; Ostermann‐Miyashita, Emu‐Felicitas; Wenz, Elena; Eufemia, Luca; Hermanns, Till; Klose, Moritz; Spyra, Marcin; et al.
Abstract: As wild areas disappear and agricultural lands expand, understanding how people and wildlife can coexist becomes increasingly important. Human–wildlife conflicts (HWCs) are obstacles to coexistence and negatively affect both wildlife populations and the livelihood of people. To facilitate coexistence, a number of frameworks have been developed to both understand the drivers of conflict and then to find solutions that mitigate conflict. However, each framework has different foci and strengths in particular stages of analysis. Here, we propose an integrated framework that leverages the individual strengths of previously fairly isolated methodologies, allowing for holistic HWC analysis. The framework for participatory impact assessment ( FoPIA ) provides a toolset for developing wildlife scenarios, selecting assessment indicators and assessing the impact of different scenarios. The social‐ecological framework of ecosystem services and disservices ( SEEDS ) analyzes the ecosystem services trade‐offs related to scenarios, and the 3i stakeholder analysis approach, supports the identification of stakeholders and provides a mechanism to explore, in detail stakeholders' interests, relative influence, and how outcomes of research are likely to impact different stakeholders. We apply these approaches to eastern Germany, where the increase in several wildlife populations (i.e., wild boar, common crane, gray wolf, and European bison) has contributed to conflict with people. We demonstrate the complementarity of FoPIA, SEEDS, and 3i in identifying stakeholder needs and showing how wildlife dynamics may affect coexistence and create imbalanced ecosystem service and disservice distributions. The integrated framework introduced here provides guidelines for analyzing the multistage process of stakeholder participation and enables a comprehensive approach to the complex challenge of HWCs.